Management of the non-traumatic full thickness rotator cuff tear - Gwilym, S; Rees, J (2012)
Approaches to the management of the torn rotator cuff vary greatly between surgeons. In response, attempts have been made to define criteria for guiding treatment. However the failings of the literature upon which these recommendations are based are well recognized and, as a result, no consensus view exists. In this article we revise the anatomy of the rotator cuff and discuss the questions we should ask in deciding which tears to treat. The non-surgical and surgical options for management of the rotator cuff tear are considered, summarizing what experimental literature is available and highlighting areas of scientific paucity. © 2011.